Noninvasive Autoregulation Monitoring in a Swine Model of Pediatric Cardiac Arrest - Lee, Jennifer K. (2012)
BACKGROUND: Cerebrovascular autoregulation after resuscitation has not been well studied in an experimental model of pediatric cardiac arrest. Furthermore, developing noninvasive methods of monitoring autoregulation using near-infrared spectroscopy (NIRS) would be clinically useful in guiding neuroprotective hemodynamic management after pediatric cardiac arrest. We tested the hypotheses that the lower limit of autoregulation (LLA) would shift to a higher arterial blood pressure between 1 and 2 days of recovery after cardiac arrest and that the LLA would be detected by NIRS-derived indices of autoregulation in a swine model of pediatric cardiac arrest. We also tested the hypothesis that autoregulation with hypertension would be impaired after cardiac arrest. METHODS: Data on LLA were obtained from neonatal piglets that had undergone hypoxic-asphyxic cardiac arrest and recovery for 1 day (n=8) or 2 days (n=8), or that had undergone sham surgery with 2 days of recovery (n=8). Autoregulation with hypertension was examined in a separate cohort of piglets that underwent hypoxic-asphyxic cardiac arrest (n=5) or sham surgery (n=5) with 2 days of recovery. After the recovery period, piglets were reanesthetized, and autoregulation was monitored by standard laser-Doppler flowmetry and autoregulation indices derived from NIRS (the cerebral oximetry [COx] and hemoglobin volume [HVx] indices). The LLA was determined by decreasing blood pressure through inflation of a balloon catheter in the inferior vena cava. Autoregulation during hypertension was evaluated by inflation of an aortic balloon catheter. RESULTS: The LLAs were similar between sham-operated piglets and piglets that recovered for 1 or 2 days after arrest. The NIRS-derived indices accurately detected the LLA determined by laser-Doppler flowmetry. The area under the curve of the receiver operator characteristic curve for cerebral oximetry index was 0.91 at 1 day and 0.92 at 2 days after arrest. The area under the curve for hemoglobin volume index was 0.92 and 0.89 at the respective time points. During induced hypertension, the static rate of autoregulation, defined as the percent change in cerebrovascular resistance divided by the percent change in cerebral perfusion pressure, was not different between postarrest and sham-operated piglets. At 2 days recovery from arrest, piglets exhibited neurobehavioral deficits and histologic neuronal injury. CONCLUSIONS: In a swine model of pediatric hypoxic-asphyxic cardiac arrest with confirmed brain damage, the LLA did not differ 1 and 2 days after resuscitation. The NIRS-derived indices accurately detected the LLA compared to laser-Doppler flow measurements at those time points. Autoregulation remained functional during hypertension.